2013
DOI: 10.7202/1015977ar
|View full text |Cite
|
Sign up to set email alerts
|

Résilience, appartenance et tourisme à Nain, Nunatsiavut

Abstract: Dans le cadre de notre projet de recherche sur la vulnérabilité et la résilience du tourisme dans l’Arctique, nous avons évalué les interactions entre le changement climatique et le tourisme dans les communautés de l’Arctique canadien. Dans cet article, nous nous intéressons à la capacité d’adaptation en présentant les résultats d’entrevues menées à Nain au Nunatsiavut, dans la province de Terre-Neuve-et-Labrador. Alors que de nombreux résidents ont manifesté leur enthousiasme à propos de la nouvelle désignati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Fifteen of these additional articles [19][20][21][22][23][26][27][28][29][33][34][35][36][37]39] were already covered by either the SROCC [4] or the Stewart et al review [14]. The rest [18,24,25,[30][31][32]38,40] was familiar to the authors but were not captured by the queries for several reasons such as missing databases, journal language, and spatial scope, i.e., not described as polar but northern. Together with these additions and after removal of 84 duplicate records between Scopus and WoS, the final count of records to be screened was 183.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifteen of these additional articles [19][20][21][22][23][26][27][28][29][33][34][35][36][37]39] were already covered by either the SROCC [4] or the Stewart et al review [14]. The rest [18,24,25,[30][31][32]38,40] was familiar to the authors but were not captured by the queries for several reasons such as missing databases, journal language, and spatial scope, i.e., not described as polar but northern. Together with these additions and after removal of 84 duplicate records between Scopus and WoS, the final count of records to be screened was 183.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of polar tourism and climate change research, whereas 250 individual authors are identified for the 93 studies (Figure 4), the set with the most links (n: 172) has only 53 items, signaling a lack of direct collaboration among scholars (without accounting for citations). A significant cluster (dark green, n: 21) is formed among mostly Canada affiliated researchers, some of whom [19,20,26,27,30,31,[34][35][36][51][52][53][54]67,74,75,86,[103][104][105] bear the highest total link strengths based on the number of articles they have contributed to. Some other researchers such as de la Barre [20], Lamers [20,82], Scott [33,54], and Müller [20,56] play key roles in linking this cluster with European counterparts.…”
Section: Bibliometric Networkmentioning
confidence: 99%
See 2 more Smart Citations